Systemic amyloid light‐chain amyloidosis beyond ANDROMEDA: Diagnostic challenges and therapeutic updates - Xia Wu; Heather Landau; Jennifer E. Liu; Yihan Cao; Raymond L. Comenzo (CA: A Cancer Journal for Clinicians, 2026)
Abstract Systemic immunoglobulin light‐chain amyloidosis is a rare but life‐threatening plasma cell disorder characterized by the production of misfolded monoclonal light chains that deposit as amyloid fibrils, leading to pathologic tissue remodeling and progressive multiorgan dysfunction. Despite substantial therapeutic advances, delayed diagnosis remains common because of nonspecific presentations and the need for coordinated hematologic, pathologic, and organ‐specific evaluation. The introduction of daratumumab‐based regimens has transformed frontline therapy, whereas advances in cytogenetic profiling, measurable residual disease assessment, and transplantation strategies have informed risk‐adapted management. Emerging treatments, including BCL‐2–targeted therapy, bispecific antibodies, chimeric antigen receptor T‐cell therapy, and possibly fibril‐directed approaches, further expand the therapeutic landscape. This review summarizes contemporary concepts in the pathobiology, diagnosis, and management of systemic light‐chain amyloidosis, with an emphasis on practical diagnostic algorithms, evolving response assessment, and remaining challenges in achieving durable organ recovery and sustained survival.